Pengaruh Model Pembelajaran Knisley untuk Meningkatkan Kemampuan Pemahaman Konseptual Siswa - Icha Romadhoni, Ardamevia Rizky; Farida, Nur; Suwanti, Vivi (JRPM (Jurnal Review Pembelajaran Matematika), 2022)
This research aims to find out the impact of Knisley’s learning model to improve students’ conceptual understanding ability of circle material. Knisley’s learning model is based on well-structured knowledge to relate new concepts to students’ previous knowledge and experiences. This study is quantitative research, using quasi-experimental research methods, and the research design uses a non-equivalent control group design. In the pretest, it was obtained that tcount<ttable (1,426<2,01063) and sig. (2-tailed) > 0,05 where 0,160 > 0,05, so from the results of the pretest, it was concluded that there was no difference in conceptual understanding between the control class and the experimental class on the circle material at MTs An-Nur Bululawang. In the posttest, tcount> ttable (2.105 > 2.01063) and sig. (2-tailed) < 0.05 where 0.041 < 0.05 as a result of the post-test questions, it was determined that the control and experimental classes at MTs An-Nur Bululawang had a different conceptual grasp of the circular material. The Knisley learning paradigm can improve students' conceptual comprehension skills, according to the findings of this study, and is effective if applied in students’ mathematics learning.